Characteristics and Evolution of Non-metallic Inclusions in Metallurgical Production of GCr15 Bearing Steel - Li Weitao, Wu Fapu, Yu Guangfu, Wang Huajun, Wang Kaimin, Jia Xingyu, Tang Haiyan (Teshugang)
In order to effectively reduce and control the non-metallic inclusions in a GCr15 bearing steel produced by BOF→LF→VD→CC process and improve its product quality， the characteristics and evolution mechanism of inclusions in bearing steel produced by the whole process were analyzed firstly by methods of systematic sampling， automatic analysis and scanning of inclusions and thermodynamic calculation in the present study. The results show that the inclusions in molten steel are mainly MgO-Al2O3 and Al2O3 after the slag melting during LF stage， and they are transformed into CaO-MgO-Al2O3 and CaO-Al2O3 with the size of 1-5 μm in the end of the LF stage. The type of inclusions remains unchanged after VD soft blowing. However， the inclusion density decreases from 16.53 pcs/mm2 in the end of the LF stage to 14.02 pcs/mm2， resulting in an inclusion removal rate of approximately 15.2%. The number density of inclusions in the tundish increases to 16.39 pcs/mm2. The types of inclusions are still mainly CaO-MgO-Al2O3 and CaO-Al2O3， of which 1-2 μm and ＞ 2-5 μm size accounted for 62.8% and 35.6%， respectively. The number of CaS-containing compound inclusions in the billet increases significantly. Thermodynamic calculation explains the evolution causes of the above inclusions. It is found that when the w［Al］s is at 0.02%， the stable existence of MgO-Al2O3 is associated with a significant variation in Mg content， ranging from 0.000 3% to 0.01%， which facilitates the formation of MgO-Al2O3 or CaO-MgO-Al2O3 type inclusions during the production of GCr15 bearing steel. The T.Ca/T.O ratios of the molten steel in LF ending， VD soft blowing process， and tundish were observed to be 0.39， 1.0， and 0.62， respectively； these values align with the theoretical （T.Ca）/（T.O） ratio range （0.13 to 1.25） conducive to the formation of five distinct types of calcium aluminate. As a result， a substantial quantity of calcium aluminate inclusions was detected. During the cooling process of the molten steel， a transformation of inclusions occurs. The liquid calcium aluminate inclusions diminishes， while the quantities of MgO·Al2O3 and CaS inclusions markedly increases.